USE OF DAA IN PATIENTS WITH HCV-ASSOCIATED LIVER DAMAGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
190 patients were observed, including 135 with a diagnosis of chronic hepatitis C (CHC) and 55 with a diagnosis of viral liver cirrhosis. Of these, 103 patients had genotype 1b, 48 had genotype 1a, 16 had genotype 3a, 10 had genotype 3a/b, and 13 had genotype 2. All patients underwent quantitative HCV viral load determination using PCR. The level of liver fibrosis was also determined using a non-invasive method called fibroscan. Patients were prescribed direct-acting antiviral drugs (DAA) for antiviral therapy.